2008
DOI: 10.1096/fj.07-105395
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of energy substrate utilization and hepatic insulin sensitivity by phosphatidylcholine transfer protein/StarD2

Abstract: Phosphatidylcholine transfer protein (PC-TP, also known as StarD2) is a highly specific intracellular lipid binding protein with accentuated expression in oxidative tissues. Here we show that decreased plasma concentrations of glucose and free fatty acids in fasting PC-TP-deficient (Pctp(-/-)) mice are attributable to increased hepatic insulin sensitivity. In hyperinsulinemic-euglycemic clamp studies, Pctp(-/-) mice exhibited profound reductions in hepatic glucose production, gluconeogenesis, glycogenolysis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(83 citation statements)
references
References 51 publications
10
71
2
Order By: Relevance
“…Although the predicted phenotype(s) was not observed with the Pctp K/K mice, new data indicate STARD2/PCTP functions in insulin-regulated pathways to maintain glucose homeostasis (Scapa et al 2008, Shishova et al 2011. Fasting serum glucose and free fatty acid levels are significantly decreased in Pctp K/K mice compared with wild-type counterparts due to increased insulin sensitivity (Scapa et al 2008). In addition, hepatic SREBP1c expression is decreased in Pctp K/K mice along with downstream target gene expression for enzymes within the fatty acid biosynthesis pathway.…”
Section: Stard2/pctp and Insulin Resistancementioning
confidence: 87%
“…Although the predicted phenotype(s) was not observed with the Pctp K/K mice, new data indicate STARD2/PCTP functions in insulin-regulated pathways to maintain glucose homeostasis (Scapa et al 2008, Shishova et al 2011. Fasting serum glucose and free fatty acid levels are significantly decreased in Pctp K/K mice compared with wild-type counterparts due to increased insulin sensitivity (Scapa et al 2008). In addition, hepatic SREBP1c expression is decreased in Pctp K/K mice along with downstream target gene expression for enzymes within the fatty acid biosynthesis pathway.…”
Section: Stard2/pctp and Insulin Resistancementioning
confidence: 87%
“…Initial studies of PCTP disruption showed no difference in phospholipid metabolism ( 23 ). However, when pushed with a lithogenic diet, PCTP knockouts showed an impaired excretion of lipid into bile and an improper balance in the bile of cholesterol to phospholipids ( 24,25 ). Mice with MLN64 mutations also have no apparent abnormalities in lipid metabolism or storage when pushed with a chow, highcholesterol, or high-fat diet ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study was motivated by the observation that Pctp Ϫ / Ϫ mice utilize fatty acids almost exclusively as an energy substrate ( 8 ). Because in small animals, brown fat consumes half or more of calories and oxygen ( 13 ), we reasoned that BAT physiology might yield key insights into metabolic regulation in Pctp Ϫ / Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type and Pctp Ϫ / Ϫ littermate control mice on an FVB/NJ genetic background ( 8 ) were housed (two to fi ve mice/cage) in an animal facility with a 12 h light/dark cycle and maintained on a standard rodent diet 5001 (LabDiets, St. Louis, MO). The temperature of the animal facility was maintained at 22 ± 1°C.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation